2010
DOI: 10.1128/jcm.00648-10
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Salmonella enterica Serotype Paratyphi A Azithromycin Resistance Leading to Treatment Failure

Abstract: The prevalence of Salmonella enterica serotype Paratyphi A infection is increasing, and multidrug resistance is a well-recognized problem. Resistance to fluoroquinolones is common and leads to more frequent use of newer agents like azithromycin. We report the first case of azithromycin resistance and treatment failure in a patient with S. Paratyphi A infection. CASE REPORTA 48-year-old male doctor presented to the accident and emergency department with a 2-week history of rigors, fever, and lethargy following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 17 publications
0
49
3
Order By: Relevance
“…[36] All isolates in our study were sensitive to ceftriaxone in contrast to some studies that reported resistance to ceftriaxone. [37,38] A limitation of our study was that clinical outcomes were not analysed. Quinolones may remain effective despite in vitro resistance and ceftriaxone may be associated with prolonged time to fever resolution despite in vitro sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…[36] All isolates in our study were sensitive to ceftriaxone in contrast to some studies that reported resistance to ceftriaxone. [37,38] A limitation of our study was that clinical outcomes were not analysed. Quinolones may remain effective despite in vitro resistance and ceftriaxone may be associated with prolonged time to fever resolution despite in vitro sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all the isolates tested were resistant to nalidixic acid (NAR), which is a very serious matter of concern posing challenge in effective treatment and management of these infections. Other treatment options for enteric fever includes azithromycin, a microcline antimicrobial, used widely now a day with good clinical response because of intra cellular accumulation of the drug [ 7,14]. Unfortunately, some authors have reported resistance to azithromycin too from different parts of the world [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment options for enteric fever includes azithromycin, a microcline antimicrobial, used widely now a day with good clinical response because of intra cellular accumulation of the drug [ 7,14]. Unfortunately, some authors have reported resistance to azithromycin too from different parts of the world [14][15][16][17]. Based on the results of our study, especially low level resistance observed towards first line antimicrobials used in the treatment of enteric fever, it can be suggested that these can be recommended either alone or in combination with cephalosporin or azithromycin as part of empirical treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations